ESTIMATIVA DE PERDAS DE FÓSFORO CAUSADAS POR EROSÃO HÍDRICA SOB CONDIÇÕES DE CHUVA NATURAL - MONTEIRO, F. D. N.; SCHMITT, M. H. S.; FERNANDES, D. S.; MENEZES, R. S.; PANACHUKI, E. (ANAIS DO ENIC, 2016)
-